IMPROVING DELIVERY SERVICE QUALITY OF LOCAL LOGISTIC SERVICE PROVIDER (LSP) COMPANY USING THE SIX SIGMA DMAIC METHODOLOGY - Abdul Hakim Amiranto (CV. Radja Publika, 2024)
This study focuses on improving the delivery service quality and operational performance of PT Jaya Connect Transportindo (PT JCT), a local logistics provider specializing in last-mile delivery for telecommunications equipment. Currently, PT JCT is facing several challenges, including a 9% defect rate and a sigma level of 3.38, resulting in a 91% service level performance. This performance falls short of the company’s goal to achieve a 4% defect rate and a 95% service level, which is the benchmark set by its top competitors. Key issues affecting PT JCT’s performance include a lack of operational staff, heavy reliance on a small number of partners, outdated tracking methods, and the absence of a system to evaluate partner performance. To address these challenges, this study applies the Six Sigma DMAIC methodology—Define, Measure, Analyze, Improve, and Control. Using tools such as the Fishbone Diagram, Statistical Process Control, and Process Capability Analysis, the research identifies the root causes of delivery issues, grouped into five categories: Man, Material, Method, Measurement, and Machine. The study proposes several practical solutions: adding more operational staff, expanding the network of delivery partners, introducing a real-time GPS tracking system, implementing a performance evaluation system for partners with clear KPIs, and ensuring vehicle reliability through regular inspections. These improvements are accompanied by a structured implementation plan to ensure their successful execution and long-term sustainability. By adopting these solutions, PT JCT can significantly reduce its defect rate, improve service quality, and achieve its performance targets. This research highlights how logistics companies can use Six Sigma tools to overcome operational challenges, enhance customer satisfaction, and maintain a competitive edge in a demanding market.